Poly[4-pyridinyl-4´-(2-methacryloyloxyethoxy)styryl ketone-co-2- hydroxypropyl methacrylate]: Synthesis, Characterization, Thermal and Electrical properties, and Photocrosslinking behavior - Aygün, Ela Nur; Coşkun, Mehmet Enes (My University, 2018)
Synthesis of a chalcone bearing pyridine ring, 4-pyridinyl-4´-(2-hydroxyethoxy)styryl ketone, wascarried out from the reaction of 4-acetyl pyridine and 4-(2-hydroxyetoxy)benzaldehyde in an aqueous solutionof NaOH. 4-Pyridinyl-4´-(2-methacryloyloxyethoxy)styryl ketone which is the methacrylate monomer bearingchalcone structure in side chain, was obtained from acylation of 4-pyridinyl-4´-(2-hydroxyethoxy)styryl ketonewith methacryloyl chloride in the cold. The copolymer of 4-pyridinyl-4´-(2-methacryloyloxyethoxy)styryl ketoneand 2-hydroxypropyl methacrylate was prepared by free radical polymerization in presence of AIBN at 70 oC.FTIR, 1H-NMR and 13C-APT spectroscopic techniques were used for structural characterization of the Chalcone,the monomer and the copolymer. Thermal characterization of the copolymer was carried out using DSC andTGA techniques. DSC curve shows that this copolymer has a glass transition temperature of 78 oC. The TGAcurve shows that decomposition given volatile product started at 230 °C and a residue of 21% left at 500 °C.Dielectric constant (?´) of the copolymer decreased rapidly from 8.8 to 4.2 with increasing frequency in the rangeof 100-1000 Hz, and after this frequency ?´ quantity remained constant at a value such as 4.2. ?´ Value of thecopolymer increased only from 4.2 to 4.9 with increasing from 290 K to 385 K. The AC conductivity of thecopolymer increases from 5.01x10-10 S/cm to 126.0x10-10 S/cm as the frequency increase from 100 Hz to 5000Hz. The AC conductivity increases slightly with increasing temperature, 2.52x10-9S/cm at 300 K, and 2.89x10-9S/cm at 385 K. After a solution of the copolymer was irradiated using UV light at 365 nm at room temperature,the absorption band at 356 nm disappeared and a new band was seen at 284 nm.
Keywords: Kimya; Uygulamalı; Kimya; Organik; Malzeme Bilimleri; Özellik ve Test